Gambaran Histopatologi Otot Korpus Kavernosum Tikus Wistar (Rattus norvegicus) Hiperlipidemia - Permatasari, Anak Agung Ayu Putri; Sari, Ni Kadek Yunita; Widhiantara, I Gede (Metamorfosa: Journal of Biological Sciences; Vol 5 No 2 (2018), 2018)
This study aims to see the histopathology of muscle corvus cavernosum penis wistar rats ( Rattus novergicus ) hyperlipidemia seen in terms of thickness and picture of tissue abnormalities. Hyperlipidemia is a risk factor for erectile dysfunction ateriosklerosis in men. This research is an experimental research with one group prettest - posttest design. Samples in this study were 10 adult male aged 3-4 months wistar rats with a weight range 150-200 grams. Prior to treatment, surgery was performed for histopathology of 5-tailed rat samples at pretest. After that, sample were made with hyperhidemia by feeding fat for 50 days. Then performed surgery for histopathological preparation of corvus cavernosum muscle in posttest. The results showed that the thickness of the corvus cavernosum of the penile mouse of hyperlipidemia decreased significantly (P?0,05) when compared with the pretest group. In the histopathologic picture occurs muscle atrophy and the existence of abnormal structures of fibrotic and collagen tissue.